EFEKTIVITAS KEBIJAKAN ZERO BALIHO DALAM PERSPEKTIF TEORI GOOD GOVERNANCE DI BALI - Karimica, Yovela Poppy Olethea Unwana Hubby; Erawan, I Ketut Putra; Erviantono, Tedi (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This paper examines the effectiveness of the Zero Baliho policy in Bali through the lens of good governance principles. The Zero Baliho initiative aims to enhance public space aesthetics and promote environmental sustainability by eliminating billboards. Key elements of good governance such as participation, transparency, accountability, and responsiveness, are analyzed in the context of this policy. Community involvement is crucial for fostering a collective awareness of environmental preservation, while transparent communication about the policy's goals and budget allocation builds public trust. Furthermore, the government's accountability in enforcing the policy and its responsiveness to community feedback are essential for ensuring its relevance and effectiveness. The potential economic impact on local businesses reliant on advertising revenue is also considered, highlighting the need for alternative support mechanisms. Ultimately, the success of the Zero Baliho policy hinges on the government's ability to effectively implement good governance principles, positioning this initiative as a model for sustainable development in other regions.